Quantitative Microbiological Risk Assessment: Underrated Tool in Process Improvement in Food Microbiology - Essam Eissa Mostafa (Journal of Food Science and Hygiene, 2018)
This article advocates for routine use of quantitative microbiological risk assessment to strengthen process control. It illustrates how modeling hazard levels and uncertainty informs critical limits, verification, and continuous improvement.